Debates of the House of Assembly / Union of South Africa - South Africa Parliament (Cape Town, 1940)
Debates of the House of Assembly of the Union of South Africa as reported in the Cape Times. Debates of the House of Assembly /Union of South Africa = Debatten van de Volksraad / Unie van Zuid-Afrika.
108 v. South Africa Politics and government.
Keywords: Index to Subjects; Additional estimates (motion - Mr Hofmeyr); Wool; Index to Speeches; Abrahamson, Mr H (Weenen); Wolfaard, Mr G van Z (Worcester); 1940; Vol. 39; JC044699; House of Assembly